2003
DOI: 10.4314/ad.v28i2.22176
|View full text |Cite
|
Sign up to set email alerts
|

3 - Globalisation and Industrial Performance in Nigeria

Abstract: This paper examines the impact of the neo-liberal globalisation of African economies on industrial performance in Nigeria. Evidence from the study indicates that, contrary to claims by the World Bank, the economic performance of firms in the manufacturing sector during the globalisation period in the study was adversely affected by the process. The study confirms the position that the globalisation project that aims at the structural economic transformation of modern capitalist relations in Africa is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…For instance, Udeaja (2003) has shown that although the two (insurance) firms investigated recorded a significant increase in taxation after privatisation, there was a positive improvement in wage income, the share of wage income in the value-added of the firms and the share of workers' wages to the company's overall value-added. Perhaps Onyeonoru (2003), on globalisation and industrial performance, is instructive here. He found out that economic performance of firms in the manufacturing sector during the globalisation period in the study was adversely affected; however, his findings were however limited to the firms in the food, beverages, and tobacco industry sub-sector.…”
Section: Production Subcontracting Experiencementioning
confidence: 99%
“…For instance, Udeaja (2003) has shown that although the two (insurance) firms investigated recorded a significant increase in taxation after privatisation, there was a positive improvement in wage income, the share of wage income in the value-added of the firms and the share of workers' wages to the company's overall value-added. Perhaps Onyeonoru (2003), on globalisation and industrial performance, is instructive here. He found out that economic performance of firms in the manufacturing sector during the globalisation period in the study was adversely affected; however, his findings were however limited to the firms in the food, beverages, and tobacco industry sub-sector.…”
Section: Production Subcontracting Experiencementioning
confidence: 99%
“…Adeniran ( 2005 ) and Onyeonoru (2003) in their research observed a unidirectional causality that runs from GDP to Electricity consumption in Nigeria. In their separate work, they both observed that electricity production in Nigeria was sub-optimal and below the installed capacity utilization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Onyeonoru (2003) arrived at very much the same conclusion in an impressive study of globalisation and industrial performance in Nigeria. Specifically, he links globalisation to tendencies towards de-industrialisation in Nigeria.…”
Section: Discussion and Conclusion: The Labour -Globalisation Interfacementioning
confidence: 75%